1995
DOI: 10.1006/jcss.1995.1083
|View full text |Cite
|
Sign up to set email alerts
|

Emptiness Problems of eNCE Graph Languages

Abstract: We consider the complexity of the emptiness problem for various classes of graph languages de ned by eNCE (edge label neighborhood controlled embedding) graph grammars. In particular, we show that the emptiness problem is undecidable for general eNCE graph grammars, DEXPTIME-complete for con uent and boundary eNCE graph grammars, PSPACE-complete for linear eNCE graph grammars, NLcomplete for deterministic con uent, deterministic boundary, and deterministic linear eNCE graph grammars. The exponential time algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…In an earlier version of this paper [19], we have shown that even every confluent eNCE graph grammar can be transformed into an equivalent neighborhood-preserving grammar, see also [11,Theorem 1.3.33]. Similarly, it has been shown in [18] that every confluent eNCE graph grammar can be transformed into an equivalent nonblocking grammar, see also [11,Theorem 1.3.21].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In an earlier version of this paper [19], we have shown that even every confluent eNCE graph grammar can be transformed into an equivalent neighborhood-preserving grammar, see also [11,Theorem 1.3.33]. Similarly, it has been shown in [18] that every confluent eNCE graph grammar can be transformed into an equivalent nonblocking grammar, see also [11,Theorem 1.3.21].…”
Section: Introductionmentioning
confidence: 89%
“…It is well known that the confluent, nonblocking, and unrestricted eNCE graph languages form a proper hierarchy [3,8]. Furthermore, every confluent eNCE graph grammar can be transformed into an equivalent nonblocking grammar [18], see also [11,Theorem 1.3.21].…”
Section: Skodinis and Wankementioning
confidence: 99%
See 2 more Smart Citations
“…It is shown in [SW1] that for every C-edNCE grammar an equivalent nonblocking C-edNCE grammar can be constructed. This fact will not be used, but will be a consequence of our proofs (cf.…”
Section: Figmentioning
confidence: 99%